Deskripsi Keterampilan Proses Sains Peserta Didik dalam Pembelajaran Menggunakan Modul Sistem Koloid Berbasis Inkuiri Terbimbing - Adilah Afikah; Iryani Iryani (Universitas Negeri Padang, 2020)
The purpose of this study is to get an overview of the Science Process Skills of students in learning using the Guided Inquiry-based Colloidal System module. The type of research used is library research with descriptive analysis. The data used in this study are secondary data, i.e. scientific journals which are in the form of articles. The data collection method is in the form of a documentation method with data analysis techniques, namely content analysis. Based on the results of a journal review that has been done, it is obtained that the use of the Guided Inquiry-Based Colloidal System module in learning especially in practical activities can bring up the Science Process Skills of students well. Each Science Process Skill indicator appears with different percentages in either category.